Peer Social Support and Self-Control Predict Student Learning Motivation: Dukungan Sosial dari Teman Sebaya dan Pengendalian Diri Memprediksi Motivasi Belajar Siswa - Azmi Syaikha Az Zahro Purnomo; Eko Hardi Ansyah (Academia Open, 2025)
General Background: Learning motivation represents a fundamental psychological factor that drives students to achieve educational goals and sustain academic engagement. Specific Background: Learning motivation among university students is shaped by internal factors such as self-control and external factors such as peer social support, both of which are essential in supporting academic persistence and achievement. Knowledge Gap: Previous studies predominantly examine learning motivation among school students or separately analyze peer social support and self-control, with limited investigation integrating both variables simultaneously among university students. Aims: This study aims to examine the relationship between peer social support and self-control with learning motivation among students at Muhammadiyah Sidoarjo University. Results: Using inferential quantitative methods with accidental sampling of 252 students, data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The findings revealed a statistically significant relationship between peer social support and self-control with learning motivation (R = 0.732; R² = 0.536; p < 0.001). Peer social support contributed 22.6% and self-control contributed 31% to learning motivation, indicating self-control as the stronger predictor. Novelty: This study integrates internal and external psychological determinants simultaneously within a university student population, providing empirical evidence on their combined relationship with learning motivation. Implications: The findings highlight the importance of strengthening peer-based support systems and fostering self-regulation competencies to support student learning motivation in higher education contexts. Highlights: Combined Internal Regulation and Interpersonal Assistance Explained 53.6% Variance in Academic Drive. Individual Behavioral Regulation Contributed a Larger Predictive Proportion Than Social Assistance. Student Academic Drive Was Statistically Associated With Both Interpersonal and Personal Psychological Factors. Keywords: Peer Social Support, Self-Control, Learning Motivation, University Students, Multiple Linear Regression